Prolonged bleeding due to a medicinal leech bite: another treatment method, primary suture. (16th July 2012) - Zengin, Suat; Yarbil, Pinar; Kilic, Hasan; Al, Behçet
Abstract : Medicinal leeches have been used in the treatment of many diseases for thousands of years. A 25-year-old man presented to our emergency department with bleeding from right and left side of his neck. He had applied leeches10 h previously to both sides of his neck to treat acne. The bleeding was not controlled by applying pressure with sterile gauze upon the wounds. Homeostasis was achieved by primary suture under local anaesthesia. Prolonged bleeding can be seen following medical leech application. In such cases, bleeding can be controlled by primary suture.